Bahaji Urang Banjar Culture As A Representation Of Local Wisdom In An Anthropolinguistic Perspective - Jahdiah; Yayuk, Rissari; Hidayatullah, Dede (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Bahaji culture in the Banjar community is one of the socio-cultural phenomena that is not only related to the implementation of the Hajj , but also contains strong local wisdom values and is inherited from generation to generations . In practice , Bahaji is not only interpreted as a religious obligation , but also as a symbol of social status, cultural identity , and a means of strengthening community solidarity . However , studies that relate Bahaji cultural practices to anthropolinguistic perspectives , especially through lexicon analysis and symbolic meaning , are still relatively limited . The formulation of the problem in the research is , 1) what rituals are carried out before and after Bahaji in the Banjar community . 2) what lexicon is contained in the Baaji culture of Banjar people 3). What value of local wisdom is contained in the Bahaji culture . This study uses a qualitative descriptive method with an ethnographic approach . The results of the study show that the lexicon in bahaji culture not only functions as a means of communication , but also as a symbol that represents the values of religiosity , social solidarity , and cultural identity of the Banjar people . Thus , Bahaji culture can be understood as a representation of local wisdom that Strengths the relationship between language , culture , and social practices in the life of the Banjar people .